2017
DOI: 10.1177/1098612x17705227
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional quantitative RT-PCR study of feline coronavirus viremia and replication in peripheral blood of healthy shelter cats in Southern California

Abstract: Objectives The objectives of this study were to determine the prevalence of feline coronavirus (FCoV) viremia, and its replication in peripheral blood using quantitative RT-PCR (qRT-PCR) methodology in a population of 205 healthy shelter cats in Southern California, as well as to assess any possible connection to longitudinal development of feline infectious peritonitis (FIP). Methods The study was performed on buffy-coat samples from EDTA-anticoagulated whole blood samples of 205 healthy shelter cats. From 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…No increase in virus shedding could be found in any of these cats, indicating that stress had no influence on FCoV shedding in the examined population [43]. Although a shelter environment is assumed to be more stressful for cats than a breeding cattery environment, the prevalence of FCoV shedding in this population was higher than many of the prevalence previously reported from shelters [16,20,23,54]. Thus, also a breeding cattery environment with more than five cats might represent a stressful situation for the individual animal.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…No increase in virus shedding could be found in any of these cats, indicating that stress had no influence on FCoV shedding in the examined population [43]. Although a shelter environment is assumed to be more stressful for cats than a breeding cattery environment, the prevalence of FCoV shedding in this population was higher than many of the prevalence previously reported from shelters [16,20,23,54]. Thus, also a breeding cattery environment with more than five cats might represent a stressful situation for the individual animal.…”
Section: Discussionmentioning
confidence: 66%
“…The prevalence of FCoV shedding has been investigated in several countries by testing fecal samples or rectal swabs for FCoV RNA by reverse transcriptase polymerase chain reaction (RT-PCR), and the results range from 31.8% to 100.0% [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Crowded living conditions and sharing litter boxes have been discussed as predisposing factors, but there are only a limited number of studies prospectively evaluating risk factors for FCoV shedding.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, they are not able to distinguish between enteric and virulent FCoVs, since no specific genetic markers have been identified for the latter strains. In addition, the enteric FCoVs have been proven to cause transient viremia and even have a low replication in the blood (Can-Sahna et al, 2007;Kipar et al, 2010;Fish et al, 2017), thus potentially being able to passively spread to the effusions associated to other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, over the years, it has been shown that FCoV RNA could also be detected in the blood of asymptomatic cats and cats with diseases other than FIP [143,144]. Several studies evaluating the use of RT-PCR in serum, plasma or whole blood confirmed this finding of possible FCoV viremia in cats without FIP [16,80,106,145,146,147]. Additionally, a recent study demonstrated that FCoV viremia does not even predict the development of FIP, as none of the healthy cats that tested positive for genomic or replicating FCoV developed FIP or clinical illness within six months of testing [147].…”
Section: Detection Of Fcov Rna By Reverse Transcriptase Polymerasementioning
confidence: 99%